2015
DOI: 10.3109/10428194.2015.1091928
|View full text |Cite
|
Sign up to set email alerts
|

A prospective analysis of blood donation history and risk of non-Hodgkin lymphoma

Abstract: Blood donation may influence subsequent NHL development via temporary immune system alterations. To test the hypothesis that frequent blood donation is associated with an increased risk of NHL and its most common histologic subtypes, we followed 36,576 men in the Health Professionals Follow-up Study (HPFS), who provided information on frequency of blood donation in the past 30 years in 1992. We confirmed 544 incident cases of NHL through 2010. Cox proportional hazards regression was used to calculate hazards r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…We will compare the incidences and risk of outcomes in donors according to the frequency of donations and compare to the non‐donor population. There are limited number of studies examining the long‐term impact of whole blood donation on risk of cancers , cardiovascular diseases and plasma donation on risk of adverse bone health and the results reported from these studies are inconsistent. Thus, the EDV:Link study is in a strong position to contribute to long‐term donor health research by using comprehensive risk factor information in participants at baseline and follow‐up through the 45 and Up Study questionnaires and by following the cohort for health outcomes using data linkages with other healthcare data sets.…”
Section: Discussionmentioning
confidence: 99%
“…We will compare the incidences and risk of outcomes in donors according to the frequency of donations and compare to the non‐donor population. There are limited number of studies examining the long‐term impact of whole blood donation on risk of cancers , cardiovascular diseases and plasma donation on risk of adverse bone health and the results reported from these studies are inconsistent. Thus, the EDV:Link study is in a strong position to contribute to long‐term donor health research by using comprehensive risk factor information in participants at baseline and follow‐up through the 45 and Up Study questionnaires and by following the cohort for health outcomes using data linkages with other healthcare data sets.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the observed association between blood donation and long‐term health outcomes across the studies were inconsistent. Several studies showed blood donation has a protective effect on CVD, cancer, and death, 5–7,10,11,13,19,21,23,29 while other studies showed blood donation had no association with CVD, cancer, and death 9,12,15,17,18,21,24,25,31 . Some studies also found that apheresis donation was associated with reduction in bone mineral density (BMD) and increased risk of fracture, 16,28 while other studies found no association between blood donation and BMD markers 22,26,27,30 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed blood donation has a protective effect on CVD, cancer, and death, [5][6][7]10,11,13,19,21,23,29 while other studies showed blood donation had no association with CVD, cancer, and death. 9,12,15,17,18,21,24,25,31 Some studies also found that apheresis donation was associated with reduction in bone mineral density (BMD) and increased risk of fracture, 16,28 while other studies found no association between blood donation and BMD markers. 22,26,27,30 One of the studies reported that apheresis donors had an increased risk of bacterial infection.…”
Section: Main Outcomes Reported and Confounding Factors Consideredmentioning
confidence: 99%
“…A large, randomized, controlled study of phlebotomy to maintain low‐normal iron levels in patients with symptomatic peripheral arterial disease did not find decreased mortality, myocardial infarction, or stroke . Blood donation has not been observed to provide a protective effect for cancer diagnosis . While increased ferritin levels are associated with diabetes and metabolic syndrome, pathophysiology and causation remain unclear.…”
Section: Potential Health Benefits Of Donating Bloodmentioning
confidence: 99%